Analysing coach-athlete `talk in interaction` within the delivery of video-based performance feedback in elite youth soccer - Groom, R.; Cushion, C. J.; Nelson, L. J. (Qualitative Research in Sport, Exercise and Health, 2012)
The purpose of this paper was to explore coach-athlete `talk in action` during performance analysis feedback sessions. Our goal was to examine how interactional tasks are accomplished through the use of talk. Coach-athlete interactions were recorded within six home match video-based feedback sessions, over the course of a 10-month English Premier League Academy season. Interactions within the sessions were recorded and transcribed using a conversation analysis approach. Analysis of the interactions revealed that the coach attempted to exercise control over the sequential organisation of the sessions, via asymmetrical turn-taking allocations, an unequal opportunity to talk, control over the topic of discussion within the interactions and the use of questioning to select speakers to take turns to talk. The findings are principally theorised through the work of Bertram H. Raven in an attempt to explain the social organisation of power within the institutional context. The conclusion emphasises the importance of coaches becoming more aware of the likely impact of such interactional practices upon athlete learning.